C-REACTIVE PROTEIN LEVELS AS PREDICTORS OF COVID-19 SEVERITY: A RETROSPECTIVE OBSERVATIONAL STUDY - Aruna Rani Behera; Sangeeta Panigrahy; Pulavarthi Samatha; Basava Siva Prasad Reddy (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Since its emergence in China in December 2019, SARS-CoV-2 has posed significant global health challenges due to its rapid spread and high mortality. Predicting COVID-19 severity remains difficult, with some suggesting C-reactive protein (CRP) as a potential early marker for severe cases. This study examines the relationship between CRP levels and COVID-19 severity to better manage the disease and aimed to investigate CRP’s utility in prognosticating COVID-19 to improve patient outcomes The study has included patients of more than 18 years diagnosed with COVID-19 infection by RT-PCR method and admitted in either ward or ICU or having any comorbid conditions eg: Diabetes, Hypertension.Materials and Methods: Analysis regarding serum CRP with the severity of disease was done. Among all statistical tests, Chi-square tests were used where P 100 mg/L had a higher likelihood of severe disease. The values were categorised based on the values we received after the investigation. And the patients were suffering from more severe conditions who had >100mg/L of CRP values. The severity was determined based on the symptoms and signs patients presented during their stay in hospital. The majority (76.3%) had non-severe cases, with a significant 23.7% presenting with severe symptoms. CRP values ranged, with most patients having levels between 8.01-50.0mg/L or